Ruined - Tintera, Amy (HarperTeen, an imprint of HarperCollins Publishers, 2016)
Emelina Flores has nothing. Her home in Ruina has been ravaged by war; her parents were killed and her sister was kidnapped. Even though Em is only a useless Ruined--completely lacking any magic--she is determined to get revenge by infiltrating the enemy's kingdom, posing as the crown prince's betrothed--Provided by publisher.